Vitamin D deficiency and its correlation with coronal pulp morphology changes - A preliminary study - Tapasya V Karemore; Mukta B Motwani; Madhur Gupta; Vaibhav Karemore; Trushita Banubakode; Kanchan A Ashtankar (Wolters Kluwer Medknow Publications, 2022)
Background: Vitamin D deficiency (VDD) is a pandemic and usually under-diagnosed, under-treated nutritional deficiency globally. Among the Indian population, VDD may be due to lower dietary vit D and calcium intake, low socioeconomic status, etc. VDD can manifest as delayed tooth eruption, absence of secondary dentin formation, altered coronal pulp morphology, enlarged pulp space, and high pulp horns. Radiographic changes can be detected by various advanced imaging techniques but with multiple drawbacks. Intraoral radiographs (IOPA) can be an easy, chair-side and routine method of detecting coronal pulp morphology (CPM) changes due to VDD. Aims and Objectives: To assess correlation of vit D deficiency (VDD) and changes in coronal pulp morphology (CPM) using dental radiographs among young adults. Material and Methods: 60 subjects were included in the study and divided into two groups: one with CPM changes and the second group without CPM changes. All the subjects underwent digital intraoral imaging and serum evaluation for vit D. The subjects were classified into deficient, optimal, and overdose categories. At the same time, the tooth morphology was divided into normal and chair/constricted types. Results: The correlation of vitamin D levels with the pulp horn heightof all three molars were negative and statistically insignificant. Pulp chamber height and width showed negligible and insignificant relationships with vitamin D levels. Conclusion: This study could not prove a significant correlation, but the data generated might help carry out advanced research in a related context. Using an Intraoral Periapical radiograph for evaluating VDD can also be a baseline screening in largepopulations in the future.